The Implication of Kyai’s Leadership as Regent (Bupati) Toward Regional Development Policy - Nurul Azizah (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
From its beginning, this research is believed to offer contribution to local social and political development in form of a knowledge, as its result shows findings about a leadership shifts from kyai into umara’ in local political dynamics and democracy system. Secondly, these findings about leadership concepts are very valuable for kyai who held a structural position. Therefore, this research is conducted in a location where most of the regencies are led by kyai as in Sumenep and Pamekasan regency in Madura island. Madura island is known for its paternalistic character where religious leaders play influential position as a role model in society. The result of this research indicates that, first, there’s a leadership shift from traditional into rational leadership in bureaucratic environment, whereas the bureaucracy itself were also transformed into a more traditional one as they held the recitation of kitab kuning and istighosah in town hall funded by Regional Budgets. The leadership of kyai as regent is determined by three aspect: its cultural and structural strength and its adaptability into a rational bureaucratic environment. The confirmation to the concept of leadership. Max Weber uses three types of leadership paradigm that includes traditional leadership, charismatic and also rational leadership. So does this leadership shift of kyai into politics. Kyais enter the political structure, so kyais must abide by prevailing values in this type of rational political leadership such as democracy and political technical procedures. Democracy upholds the principle of transparency and direct participation of the community. Kyais are facing two choices: to follow the traditional religious values or the values of democracy. What will happen next is not the the kyai’s choice. Key words: leadership, regent, kyai, policy, development.